CLINICAL PRESENTATIONS OF ARTERIAL HYPERTENSION DEPENDING ON THE QTc INTERVAL DURATION OF ECG - Tselik, N.; Shevchuk, M.; Martynenko, A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The relationship between the duration of the complex QTc ECG and clinical signs of arterial hypertension (AH) in 54 patients (16 men and 38 women) 1-3 degree and I-III stage, mean age 58 ± 18 years, was investigated. 3 classes of QT interval duration were allocated: classified shortened (< 320 ms), normal (> 320 ms and < 440 ms), classified prolonged (> 440 ms). The binomial distribution of frequencies of studied parameters in classes of the QTc interval for alternative criteria was determined. The duration of the QTc interval in the sampling was 350 ms – 490 ms. The proportion of the normal range (> 320 ms and < 440 ms) was 0.85, classified prolonged (> 440 ms) – 0.15. The probability of occurrence of QTc prolongation ECG increased in elderly patients, obesity, abusing of alcohol, mild and moderate degree and stage II AH, diabetes mellitus, atherosclerotic cardiosclerosis, stable angina functional class (FC) II, HF FC III and II A stage. Dependencies of the elongated QTc of ECG from the sex of the patients have not been established.